Pengaruh Open Banking berbasis Open API terhadap Eksistensi Perbankan - Muqorobin, Masculine Muhammad; Anggraini, Ayu; Rahmawati, Ayu Dwi; Yohanes, Diana; Ifkarina, Faricha Dzakia (Universitas Muhammadiyah Semarang, 2021)
Open Banking is a system that provides financial institution network data to users through an API (application programming interface). Open API gives API providers the right or ability to provide consumer data access to API users with consumer consent. This study aims to determine the readiness of banks in Indonesia to implement Open Banking based on Open API. The method used is a qualitative phenomenological approach by collecting various data, analyzing, and describing the results of the analysis. The results of this study indicate that Indonesia can implement Open Banking based on the Open API by conducting an assessment of countries that have implemented it such as the UK, in order to encourage digital progress in the Banking industry so as to create connectivity between banks and Payment System Service Providers (PJSP) through open Banking.